Physicochemical characterization of ferric carboxymaltose brands in India: relevance to anemia management in chronic kidney disease - Tandayam, Abhishek; Singh, Tarun; Venkatesh, P.; Muchhala, Snehal Sameer; Kotak, Bhavesh P. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Ferric carboxymaltose (FCM) is widely used in the management of anemia associated with chronic kidney disease. The therapeutic efficacy and long-term safety of FCM related to free iron mediated toxicity can be influenced by its physicochemical properties. This study aimed to compare physicochemical properties across various FCM brands available in India. Methods: Samples of FCM from 6 different manufacturers were procured including Dr. Reddy’s FCM brand injection Irny and subjected to a series of laboratory tests. Key quality attributes like carbohydrate content, molecular weight, etc. were analysed using validated methodologies and compared with USFDA reference-listed drug (RLD) Injectafer. Results: The carbohydrate content of Dr. Reddy’s injection Irny (8.78%) was comparable to USFDA RLD (8.2%), whereas other brands showed variability ranging from 4.38% to 10.56%. Molecular weight of Irny (2.74 lakh) was also in line with USFDA RLD (2.94 lakh), with other brands mostly exhibiting lower molecular weights. Zeta potential of injection Irny (0.17 mV) closely matched that of USFDA RLD (1.25 mV), while other brands showed more negative values ranging from -0.70 mV to -27 mV. Degradation kinetics (T75 value) of injection Irny (19.14 minutes) were similar to USFDA RLD (18.34 minutes), while other brands demonstrated longer degradation times (21 to 52 minutes). Conclusions: Study highlighted notable variability in physicochemical properties of different FCM brands. Dr. Reddy’s injection Irny closely aligns with the USFDA RLD Injectafer quality attributes, suggesting comparable potential clinical outcomes and long-term safety. The observed differences among other brands may influence their bioequivalence and long-term safety.